Longevity extension of worker honey bees (Apis mellifera) by royal jelly: optimal dose and active ingredient - Yang, Wenchao; Tian, Yuanyuan; Han, Mingfeng; Miao, Xiaoqing (PeerJ, 2017)
In the Western honey bee, Apis mellifera, queens and workers have different longevity although they share the same genome. Queens consume royal jelly (RJ) as the main food throughout their life, including as adults, but workers only eat worker jelly when they are larvae less than 3 days old. In order to explore the effect of RJ and the components affecting longevity of worker honey bees, we first determined the optimal dose for prolonging longevity of workers as 4% RJ in 50% sucrose solution, and developed a method of obtaining long lived workers. We then compared the effects of longevity extension by RJ 4% with bee-collected pollen from rapeseed (Brassica napus). Lastly, we determined that a water soluble RJ protein obtained by precipitation with 60% ammonium sulfate (RJP60) contained the main component for longevity extension after comparing the effects of RJ crude protein extract (RJCP), RJP30 (obtained by precipitation with 30% ammonium sulfate), and RJ ethanol extract (RJEE). Understanding what regulates worker longevity has potential to help increase colony productivity and improve crop pollination efficiency.
Keywords: Worker bee; Bee pollen; Royal jelly; RJP60; Longevity